A New Approach for Limited Preemptive Scheduling in Systems with Preemption Overhead - Nasri, Mitra (2016)
28th Euromicro Conference on Real-Time Systems (ECRTS 2016). 5 to 8, Jul, 2016. Toulouse, France.